P007 Novel integration of a digital patient-reported outcome measure into an NHS electronic health record. (23rd April 2022) - Neame, Matthew; Reilly, David; Bond, David; Puthiyaveetil, Ajmal; McCann, Liza; Mahmood, Kamran; Almeida, Beverley; Pain, Clare E; Furfie, Victoria; Cleary, Gavin
Abstract: Background/Aims: The Childhood Health Assessment Questionnaire (CHAQ) and 0-10cm visual analogue scale (VAS) for self-reporting global-wellbeing form part of the Core Outcome Variables measuring disease activity in juvenile idiopathic arthritis. However, reported barriers to using paper-based CHAQs include: impacts on consultation time and issues with scoring and transcribing CHAQ data into health records. To address these issues we aimed to develop a digital CHAQ (eCHAQ) for patients attending paediatric rheumatology clinics at Alder Hey Children's Hospital. Additional objectives included: developing automated invitations to complete eCHAQs; achieving automated scoring and integration of CHAQ data into the hospital's Electronic Health Record (EHR); investigating the acceptability of the eCHAQ to patients and clinical staff; and studying the effects of the system on CHAQ completion rates. Methods: The eCHAQ was developed collaboratively by the Alder Hey Information Technology team, clinicians, and a technology provider, Aire Logic. Acceptability was measured using a patient survey (patient and parent ePROM questionnaire), and a survey (Technology Acceptance Model 2 questionnaire) and focus group involving clinical staff. CHAQ completion rates were measured using a before- after study of data from clinical records. Results: The eCHAQ was implemented in April 2021 and approximately 500 eCHAQ invitations are sent monthly. Technical features include automated generation of SMS invitations to complete eCHAQs; automated scoring of CHAQ assessments; and unique URLs (webpage addresses) enabling automated re-integration of CHAQ data into the EHR. Patients/care-givers (n = 24) scored the eCHAQ highly across Likert scale items designed to assess accessibility (median response = 5 [strong agreement]; interquartile range [IQR] = 0); and acceptability (median response = 5 [strong agreement]; IQR = 0). Clinical staff (n = 7; consultants, nurse specialists and occupational therapists) also scored the eCHAQ highly across domains tested using Likert scale items including "Perceived Usefulness" (median response = 7 [strong agreement]; IQR = 0.25) and "Output Quality" (median response = 7 [strong agreement]; IQR = 1). Thematic analysis of a focus group discussion involving 10 members of the Rheumatology MDT identified that strengths of the eCHAQ system included improved access to clinical data, improved data quality and time saved. Concerns relating to access to digital technologies were highlighted. Use of the eCHAQ resulted in a significant increase in the CHAQ completion rate. Before the implementation of the eCHAQ, documentation of a CHAQ score in the EHR occurred in 33/100 (33%) assessed records compared to 47/65 (72%) after the introduction of the eCHAQ system (chi-square = 11.51; p < 0.05). Conclusion: Development of a highly-automated digital CHAQ, with integration directly into an NHS EHR, was technically feasible. Introduction of the eCHAQ was found to be highly acceptable to patients and clinical staff and was associated with a significant improvement in CHAQ completion rates. Disclosure: M. Neame: None. D. Reilly: None. D. Bond: Other; Employee of private technology provider involved in the development of the reported intervention. A. Puthiyaveetil: None. L. McCann: None. K. Mahmood: None. B. Almeida: None. C.E. Pain: None. V. Furfie: None. G. Cleary: None.